Pengaruh Capital Adequacy Ratio, Non Performing Loan dan Biaya Operasional Pendapatan Operasional Terhadap Return On Assets - Nanin Diana Hediati; Nanu Hasanuh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine whether there is an effect of CAR, NPL, and BOPO on ROA at BJB Bank for the period 2011 to 2018.The data used in this study uses secondary data in the form of BJB Bank Quarterly Published Financial Reports for the period 2011 to 2018 published by the Authority. Financial Services (OJK). The sample used is one company, namely Bank BJB as the object of research. The method used in this research is quantitative method. Tools to analyze data using multiple linear regression analysis and hypothesis testing using the t test and f test. This study uses the SPSS version 26 program to process data. The results of the research simultaneously show that the variables CAR, NPL, and OEOI have an effect on ROA. The results of the study partially show that the CAR variable has a significant positive effect on ROA, then the NPL variable has a significant positive effect on ROA, and the BOPO variable has a significant negative effect on ROA. Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operational Cost of Operating Income (BOPO), Return On Assets (ROA).